Mesoscale to Microscale Coupling for Wind Energy Applications: Addressing the Challenges. (January 2020) - Haupt, S E; Berg, L; Churchfield, M; Kosovic, B; Mirocha, J; Shaw, W
Abstract: The purpose of the US DOE's Mesoscale to Microscale Coupling (MMC) Project is to develop, verify, and validate physical models and modeling techniques that bridge the most important atmospheric scales that determine wind plant performance and reliability. The project seeks to create a new predictive numerical simulation capability that represents a range of dynamic atmospheric flow conditions impacting wind plant performance.